Timing is crucial for consequences of migratory connectivity. Issue 5 (9th November 2015) - Bauer, Silke; Lisovski, Simeon; Hahn, Steffen
Abstract : Migratory connectivity can have important consequences for individuals, populations and communities. We argue that most consequences not only depend on which sites are used but importantly also on when these are used and suggest that the timing of migration is characterised by synchrony, phenology, and consistency. We illustrate the importance of these aspects of timing for shaping the consequences of migratory connectivity on individual fitness, population dynamics, gene flow and community dynamics using examples from throughout the animal kingdom. Exemplarily for one specific process that is shaped by migratory connectivity and the timing of migration – the transmission of parasites and the dynamics of diseases – we underpin our arguments with a dynamic epidemiological network model of a migratory population. Here, we quantitatively demonstrate that variations in migration phenology and synchrony yield disease dynamics that significantly differ from a time‐neglecting case. Extending the original definition of migratory connectivity into a spatio‐temporal concept can importantly contribute to understanding the links migratory animals make across the globe and the consequences these may have both for the dynamics of their populations and the communities they visit throughout their journeys. Synthesis Migratory connectivity quantifies the links migrant animals make across the globe and these can have manifold consequences – from individual fitness, population dynamics, gene flow to transmission of pathogens and parasites. We show through the use of empirical examples and a conceptual model that these consequences not only depend on which sites are used but importantly also on when these are used. Therefore, we specify three dimensions of migration timing – phenology, synchrony and consistency, which describe the timing of migration 1) relative to development of key resources; 2) relative to the migration of other individuals; and 3) relative to previous migration events. Each of these dimensions can alter the consequences, but typically through different mechanisms.